Fighting corruption with asymmetric penalties and leniency - Johann Lambsdorff; Mathias Nell (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2007)
Corrupt arrangements are characterized by a high risk of opportunism: double-dealing, whistle-blowing and extortion are significant uncertainties for participants in corrupt transactions. This paper demonstrates how legislators may use an asymmetric design of (criminal) sanctions and leniency programs to amplify these inherent risks, thereby destabilizing corrupt arrangements. It is also shown that asymmetric penalties and (ex-ante) leniency do not necessarily interfere with the goal of deterrence and may be a useful tool to disband the 'pact of silence' characteristic of corrupt arrangements. In particular, we show that bribe-takers should less be penalized for taking and more for reciprocating a bribe. Likewise, bribe-givers should be punished for giving bribes, but not for accepting the bribetakers' reciprocity.
Keywords: K42; D73; 330; corruption; asymmetric penalties; leniency; (self-) reporting; whistle-blowing; Korruption; Kriminalpolitik; Kriminalitätsökonomik; Opportunismus; Theorie